Physical losses could partially explain modest carotenoid retention in dried food products from biofortified cassava - Bechoff, Aurélie; Tomlins, Keith Ian; Chijioke, Ugo; Ilona, Paul; Westby, Andrew; Boy, Erick (Public Library of Science, 2018)
Gari, a fermented and dried semolina made from cassava, is one of the most common foods in West Africa. Recently introduced biofortified yellow cassava containing provitamin A carotenoids could help tackle vitamin A deficiency prevalent in those areas. However there are concerns because of the low retention of carotenoids during gari processing compared to other processes (e.g. boiling). The aim of the study was to assess the levels of true retention in trans–β-carotene during gari processing and investigate the causes of low retention.